Treatment of short stature in renal disease with recombinant human growth hormone. Issue 8 (August 1990) - Rees, L; Rigden, S P; Ward, G; Preece, M A
Abstract : Six prepubertal children with chronic renal failure (group 1), six prepubertal children with renal transplants (group 2), and six pubertal children with renal transplants (group 3) who were short (mean height SD score, -3.2, range -4.5 to -1.6) and growing poorly (mean (range) growth velocity (cm/year) over the year before treatment: group 1, 4.8 (3.5-5.8), group 2, 2.3 (0.9-4.7), and group 3, 3.2 (0.5-6.5] were treated with recombinant human growth hormone 30 units/m2/week in daily doses for a median of 0.98 years (range 0.25-0.99). Mean (range) growth velocity over the treatment period increased significantly in all groups (group 1, 10.7 (8.8-12.3), group 2, 6.1 (2.7-10.8), and group 3, 6.0 (4.6-6.8]. There was, however, no improvement in height SD score for bone age in any group. The renal function of two children deteriorated after starting treatment with growth hormone, but it was not possible to say whether the growth hormone was responsible for this. The long term effects of treatment and its influence on final height are not yet known.